PROBLEMATIKA HADIS DAN ‘ULŪMUL HADĪS - Dr. Mukhlis Mukhtar (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2017)
This article describes the problems of hadith and the science of hadith.From the results of the assessment can be understood hadith is any speech, deeds, taqrir, and the exposures are leaning to the Holy Prophet, being the science of hadith is the science which deals with the ways junction hadith to the Prophet. Interms of knowing the narrator matters, regarding to the late-dhabit and justice, and in terms of connecting or breaking sanad.Hadith studies stagnation caused by: a. The issue of authenticity of hadith; b.Determination of justice hadith scholars of the companaons; c. Existence of books of Rijal al-Hadith; d. Stigma ingkar sunnah. There ara two things need to be dane in order to develop the study of hadith, the first related to the stady of hadith texts and the second related to the technical issues of teaching hadith.